High yield synthesis and optical properties of MgF2 nanowires with high aspect ratios. Issue 35 (22nd March 2016) - Abbas, Saleem; Huang, Yang; Lin, Jing; Abbas, Aumber; Xu, Xuewen; Li, Jie; Wang, Sai; Jin, Xing; Tang, Chengchun
Abstract : Ultrapure highly crystalline magnesium fluoride (MgF2 ) nanowires with high aspect ratios were successfully synthesized by utilizing ammonium boron trifluoride (NH3 BF3 ) as a precursor material for the first time. Abstract : Ultrapure highly crystalline magnesium fluoride (MgF2 ) nanowires with high aspect ratios were successfully synthesized by utilizing ammonium boron trifluoride (NH3 BF3 ) as a precursor material for the first time. Our results reveal that when the vapors of NH3 BF3 react with magnesium chloride (MgCl2 ), a perfect crystalline MgF2 phase can be obtained on a large scale. The MgCl2 utilized in this study plays a crucial role in nanowire growth and morphology control, resulting in ultrapure and highly crystalline MgF2 nanowires. The prepared nanowires have an average diameter of 60 nm and lengths up to tens of micrometers. Property studies indicate that the MgF2 nanowires are completely transparent in nature as confirmed by UV-Vis spectroscopy. We believe that these nanowires provide promising building blocks for the future optical nanodevices.